“Swiss world” in modern drama - Anisimova, Marina V. (2018)
The aim of the article is to reveal the peculiarities of “Swiss world” – its specific realities, peculiarities of mentality, national character, traditions in the new Swiss drama, i.e., Swiss dramaturgy of the late 20th - early 21st centuries (based on the work by Lucas Barfuss, Miriam Neidhart, Handl Klaus, Leo Tuor, etc.). In the modern globalized world, the borders of the national are gradually blurring, the originality and uniqueness of traditions are lost. Swiss dramatists describe this process with special keenness of observation and subtlety, because the conflict between hermeticism and openness was inherent in Switzerland throughout the history of the country. But today Switzerland as a historically “hermetic” and “neutral” country has been retaining its special status in the European world. The plays analyzed in this article speak, on the one hand, of strengthening the all-European tendencies, the similar nature of the problems facing the whole of Western society and the contradiction between reality and the national myth that represents the country as a paradise on earth, evidence, on the other hand, in favor of “the Swiss world. The article considers both tendencies – centrifugal and centripetal that characterize the current situation in Switzerland.